Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1073/pnas.0809269106
|View full text |Cite
|
Sign up to set email alerts
|

Radially expanding transglial calcium waves in the intact cerebellum

Abstract: Multicellular glial calcium waves may locally regulate neural activity or brain energetics. Here, we report a diffusion-driven astrocytic signal in the normal, intact brain that spans many astrocytic processes in a confined volume without fully encompassing any one cell. By using 2-photon microscopy in rodent cerebellar cortex labeled with fluorescent indicator dyes or the calcium-sensor protein G-CaMP2, we discovered spontaneous calcium waves that filled approximately ellipsoidal domains of Bergmann glia proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
133
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 44 publications
(55 reference statements)
12
133
0
3
Order By: Relevance
“…S2D), indicating that astrocytes were activated by our stimulation protocol across the entire field of view, rather than in a specific zone. Indeed, this increase in astrocytic calcium was not wave-like in nature, as has been observed in other systems (22,37). In both trial types, no waves were evident when plotting every transient time as a function of position from the patched astrocyte across the 4-min trial (Fig.…”
Section: Stimulation Of Individual Astrocytes Increases Network Astromentioning
confidence: 83%
“…S2D), indicating that astrocytes were activated by our stimulation protocol across the entire field of view, rather than in a specific zone. Indeed, this increase in astrocytic calcium was not wave-like in nature, as has been observed in other systems (22,37). In both trial types, no waves were evident when plotting every transient time as a function of position from the patched astrocyte across the 4-min trial (Fig.…”
Section: Stimulation Of Individual Astrocytes Increases Network Astromentioning
confidence: 83%
“…However, formation of the typically narrow and elongate PAP structure in Bergmann glia depends on Ca 2+ influx through AMPA receptors (8,15) not identified in hippocampal or cortical astrocytes (38). Here, mGluR-mediated intracellular PAP motility mechanisms might similarly work by an increase in intracellular Ca 2+ concentration through release from intracellular stores triggered by direct and indirect mGluR3 or 5 signaling (30).…”
Section: Discussionmentioning
confidence: 99%
“…At the ultrastructural level, the PAPs, although abundant in the neuropil, specifically prefer contacting synapses and dendrites versus axons (4). The synaptic wrapping is highly dynamic (5-9) and also activity-dependent even in the context of physiological functions, such as motor learning, daily fluctuations of the circadian clock, lactation, parturition, or dehydration (10)(11)(12)(13)(14)(15). Here, we asked two questions about the structural basis of glia-synaptic interaction: What is the stimulus for PAP plasticity, and what are the intracellular mechanisms accomplishing the motility and the formation of the PAP?…”
mentioning
confidence: 99%
“…Computational modeling has suggested that such synaptically induced activity would cause strikingly large depolarization (up to 40 mV) of the BG membrane processes local to the activated sites (7). Furthermore, PF burst activity elicits transient and local Ca 2+ increases in BG processes via AMPA and ATP receptor-mediated mechanisms (2,(8)(9)(10)(11). Despite the accumulating evidence of neuron-to-glia communication in the cerebellum, if the communication between these cells is a one-way relationship, the glia would only be a "listener" and it would not be able to actively participate in a layer of information processing.…”
mentioning
confidence: 99%